Android application of rapid visual screening for buildings in Indian context. (December 2022) - Nanda, Radhikesh P.; Damarla, Rithwez; Nayak, Kumbla Anupa
Abstract: Computers lessen all the laborious work, specifically by introducing software applications following mobile applications and IoT (Internet of Things) in numerous civil engineering disciplines. Prevention of forfeiture of life and property is becoming the prime agenda, and seismic vulnerability assessment of existing buildings is one of the quickest methods for an earthquake disaster mitigation plan. In this study, an attempt is made to modify the commonly used FEMA rapid visual screening score sheet concerning Indian building typology and the age of the building. Also, to make RVS further rapid an RVS tool named RVS_IND App is developed using the android App, particularly for the seismic performance evaluation of buildings at the visual inspection level. The application reduced the time taken for RVS from 15 to 20 mins per building to <2–3 mins per building and all the building score sheets can be stored during a walk down, apprising the speed of assessment of huge building stock.